The birth of bioethics and the constitution of the biopower - Junges, José Roque (Acta Bioethica, 2011)
The birth of Bioethics is associated to several persons and facts of the North American context. But this is only the surface of its origin. The article aims to show that bioethics is linked with the emerging of the management of life through the biopower with its biopolicy dynamics. The way to reach this objective is to check the authors, as Foucault, Agamben, Negri and Hardt, who analysis deeply its configurations, which are the true cause of Bioethics. Therefore the model of ethics appropriated to Bioethics is the critical hermeneutics of the biopolicy dynamics. It consists in a critical analisis of the facticity of these dynamics in its social and cultural context and in discourses constructed to its justification through the methodology of thBe depth hermeneutic proposed by Thompson. A concrete example of this result is the analysis of the right to health crossed by tecnosemiological and biopolitical agencies of the biothecnology companies.